2016
DOI: 10.1016/j.thromres.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand factor deficiency caused by LVAD is ADAMTS-13 and platelet dependent

Abstract: An in vitro model for LVAD associated aVWD demonstrated that ADAMTS-13 and platelets contribute to the depletion of HMWM of VWF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…High shear stress, which presumably unfolds the central A2 domain of ultra large plasmatic vWF, restores the sensitivity of vWF to ADAMTS13 [ 21 ]. Pump-induced shear stress in LVAD patients might therefore enhance HMWM-vWF breakdown into smaller units, leading to lower vWF activity [ 22 ]. Elevated HMWM-vWF cleavage consumes ADAMTS13 during its action on vWF [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High shear stress, which presumably unfolds the central A2 domain of ultra large plasmatic vWF, restores the sensitivity of vWF to ADAMTS13 [ 21 ]. Pump-induced shear stress in LVAD patients might therefore enhance HMWM-vWF breakdown into smaller units, leading to lower vWF activity [ 22 ]. Elevated HMWM-vWF cleavage consumes ADAMTS13 during its action on vWF [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pump-induced shear stress in LVAD patients might therefore enhance HMWM-vWF breakdown into smaller units, leading to lower vWF activity [ 22 ]. Elevated HMWM-vWF cleavage consumes ADAMTS13 during its action on vWF [ 22 ]. As a result, both vWF activity and ADAMTS13 levels decrease [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to native and prosthetic valve disease, high shear stress is also encountered with LVADs. There have been numerous studies to suggest that VWF is a player in the established association between LVAD and bleeding . Van Belle et al performed VWF analysis in patients with the HeartMate‐II LVAD (Thoratec Corporation) .…”
Section: Vwf and Lvadmentioning
confidence: 99%
“…There have been numerous studies to suggest that VWF is a player in the established association between LVAD and bleeding. 15,48,49 Van Belle et al performed VWF analysis in patients with the HeartMate-II LVAD (Thoratec Corporation). 17 The study found a significant reduction in HMWM as well as VWF:CB/ VWF:Ag ratio shortly after initiating the pump.…”
Section: Vwf and Lvadmentioning
confidence: 99%
“…Recently, an in vitro model of VAD circulation confirmed the depletion of large VWF multimers is dependent on both ADAMTS13 and platelets. 42 The diagnosis of AVWS is based on decreased VWF activity to antigen ratio and diminished or total absence of large multimer bands on VWF multimeric structure assay. However, VWF antigen and activity in these patients can be normal or even increased.…”
Section: Acquired Von Willebrand Syndromementioning
confidence: 99%